Techniques of RFID systems: Architectures and applications - Mohd, Yasin; Khaw, M. K; Reaz, M. B. I (2006)
From its first use in World War II, to differentiate between enemy and friendly aircraft, RFID has come to an era where it is used as an important identification tool, providing added security and conveniences in our daily lives. Its components and features are still being researched and integrated in existing system to create a marketable and potential new system. (1,2)The main purpose Of this article is to highlight and discuss the various RFID system that are being implemented or under development. The advances, approaches and improvements in the designs will be examined and, if possible, compared with one another Recommendations for future study are also outlined. This review serves as a comparative study and reference, beneficial for RFID researchers for future implementation of the technology.